Development and Validation of a Semiotic Project-Based Module to Support Early Childhood Numeracy Literacy - Christine Wulandari Suryaningrum; Astri Widyaruli Anggraeni; Nurul Imamah Ah; Misyana Misyana; Kuni Hikmah Hidayati (STAI Hubbulwathan Duri, 2025)
Early Childhood Education (ECE) often relies on paper-based activities that limit children’s engagement and contextual learning. To address this, a semiotic project-based module was developed to enhance early numeracy literacy through culturally relevant, hands-on learning aligned with children's developmental needs. This research employed a Research and Development (RD) design using the 4D model (Define, Design, Develop, and Disseminate). Module development included needs analysis, diagnostic assessment, media and activity design, expert validation, small- and large-scale trials, and evaluation. The module integrated semiotic elements (icons, indices, and symbols) within project-based learning themed around traditional foods from Jember, Indonesia. Validity, practicality, and effectiveness were assessed through expert review, teacher questionnaires, and observational data. Expert validation results showed an average validity score of 85%, categorized as “very valid.” Teacher responses in the small-scale trial (n=13) indicated 92.3% rated the module “very effective,” while the large-scale trial (n=13) achieved 100% in the same category. Observations of children’s participation indicated a 98% engagement rate, demonstrating high practical effectiveness. The findings suggest that the module is valid, practical, and effective in supporting early numeracy literacy. The use of semiotic representations within culturally contextualized projects provided meaningful numeracy experiences. However, the small sample size and local context limit generalizability. Further research with diverse populations and objective assessments is recommended.